The Post-translational Modifications of Smurf2 in TGF-β Signaling - Bai, Yangjinming; Ying, Ying (Frontiers in Molecular Biosciences, 2020)
Smad ubiquitin regulatory factor 2 (Smurf2), an essential negative regulator of TGF-β signaling, ubiquitinates TGF-β receptors (TβRs) and Smad proteins, inducing their proteasomal degradation. Smurf2 plays crucial roles in regulating TGF-β signaling and maintaining normal cellular functions and tissue homeostasis; dysfunction of Smurf2 triggers abnormal TGF-β signaling in pathological states. Smurf2 has been reported as a potentially strong candidate for targeting therapies for related diseases. Recent work has begun to focus on the regulation of Smurf2 itself, and emerging evidence indicates that Smurf2 is regulated by post-translational modifications (PTMs) mechanisms. These mechanisms predominantly regulate the expression level and E3 ligase activity of Smurf2, strongly suggesting that this protein contributes to complicated roles under multiple pathophysiological conditions. In this review, we cover some significant and novel mechanisms of the PTMs that potentially control Smurf2 participation in TGF-β signaling, including ubiquitylation, SUMOylation, neddylation, phosphorylation, and methylation in order to provide a broad view of the depth and sophistication of Smurf2 function in TGF-β regulation, as well as perspectives for future therapeutic directions for its associated diseases.